A CASE STUDY OF VOCABULARY ACQUISITION CHALLENGES FACED BY UZBEK LEARNERS: A MIXED RESEARCH APPROACH - Kamolova Sevara Jamol kizi; Khasanova Yulduz Mukhtor kizi (Bright Mind Publishing, 2025)
This research paper deals with investigations over major vocabulary acquisition challenges that Uzbek learners have faced, as well some alternative solutions to tackle the matter. More than 100 individuals were subjected to take part in self-made questionnaires and semi-structured interviews so as to find out key factors in difficulties of vocabulary acquisition. Both questionnaire and interviews were divided into three sub – groups, including background information of learners, exposure and practice, linguistic challenges they have met during their studies. The main reason of this division was to clarify underlying reasons of the issue deeper. Questionnaires indicated that most of individuals learned new words by only repetition, but not in the context. In addition to that most candidates with difficulties in acquiring new words claimed a lack of target language usage in their daily lives which seems to be a main barrier to handle. Furthermore, there were some specific differentiations for the culture making it difficult to acquire a language, such as phonology, syntax, word order, expressive means and stylistic devices. Having diagnosed all the data supported by questionnaires and interviews, this research paper covers some effective implementation to make learning language process easier for Uzbek students. First of all, it is recommended to pay more attention to practical usage of vocabulary with a help of exposure to English atmosphere. This will give learners an opportunity to use what they have learnt in practice.
Keywords: Diagnostic analysis, language acquisition, mixed approach.